(untitled) (Theatrum historiae, 2012)
The article describes the teaching of composition in primary schools at the turn of the 18th and 19th centuries – its range, the approaches used and the attitude of teachers. It also describes what the aim of this teaching was and what pupils took away with them. At the same time, it analyses the textbooks that were used in teaching composition.